Inovasi Pemberdayaan Masyarakat Melalui Program Aceh Kreatif Untuk Mengurangi Kemiskinan di Aceh - Agatha Debby Reiza Macella; Najamudin Najamudin; Sri Wahyu Handayani; Irma Juraida (Universitas Teuku Umar, 2021)
Aceh as one of the special autonomous regions which has a large enough budget compared to other regions makes the Aceh regional government have more useful programs to help alleviate poverty with a variety of superior programs, many regional potentials from various sectors that can be developed. The purpose of this study is to analyze the implementation of community empowerment programs through the Aceh Kreatif program so far and how the conditions of opportunities and challenges can be utilized by local governments in developing products and services from community empowerment through the Aceh Kreatif program. The research method used is a qualitative method. descriptive with the literature study technique The Aceh Creative Program is one of the 15 flagship programs of the Aceh government which indeed aims to improve the community's economy by emphasizing innovation creativity and utilizing local potential that is spread throughout the region from cities to villages in Aceh, contained in Aceh Qanun No.1 of 2019 concerning the Aceh Medium Term Development Plan (RPJM) for 2017-2022. The performance of the implementation of community empowerment through the Aceh program can be said to be good. 115 Bumdes are developing and getting turnover and obtaining PAG, several businesses were born in the village from community empowerment through the Aceh Kreatif program. Communication of the implementing agency is carried out through Focus Group discussions (FGD) then coordination meetings which are held regularly at the beginning of the year. In addition, the PMG Aceh Office conducts monitoring and evaluation of several gampongs in Aceh. Opportunities and challenges faced include central government support, competition, advances in science and technology, limited advice and infrastructure, as well as the quality and quantity of human resources.